The significance of the macerals identification for understanding and study the transformation processes of organic matter in source rocks - N. V. Pronina; A. P. Vaitekhovich; A. G. Kalmykov; D. A. Marunova (Georesursy, 2024)
The question of the correct terminology is highly relevant, since researchers should understand one another in communication with specialists in different branches of geology. An overview of the terms already existing in the English-speaking world for describing oil-prone macerals, such as alginite, bituminite, bitumen, solid bitumen, pyrobitumen, oil, was presented, and it is more convenient to combine all zooclasts into bioclasts, since it is not always possible to determine whether the remains belong to the animal or plant world. Particular difficulties emerged with the term “bitumen”, which in Russian has two meanings. Increasingly, the films between mineral grains can be named both bitumen and oil. It was also suggested to divide bituminite in pre-mature bituminite, mature bituminite and post-mature bituminite in order to emphasize the features of those transformations that occurred with the initial organic matter during thermal maturity. Due to the fact that in the process of thermal maturity, the reactive part of kerogen = bituminite will transform into a liquid and gas, its solid part (“residual organic matter”) was suggested to be called solid bitumen or pyrobitumen.